2002
DOI: 10.1002/ajp.1069
|View full text |Cite
|
Sign up to set email alerts
|

Sex identification assay useful in great apes is not diagnostic in a range of other primate species

Abstract: The ability to identify the sex of individuals from noninvasive samples can be a powerful tool for field studies. Amelogenin, a nuclear gene proximate to the pseudoautosomal region of mammalian sex chromosomes, has a 6 base-pair (bp) size difference between human X and Y chromosomes that can be PCR-amplified and sized to distinguish male from female DNA. We examined whether this test can be used to identify sex from different DNA sources across a number of nonhuman primate taxa. Using human amelogenin primers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 12 publications
(13 reference statements)
0
33
0
Order By: Relevance
“…With respect to PCR-based sex determination, for example, recently verified that the sexing assay commonly employed in human forensic cases (which is based on a 6-base-pair difference in length between homologous regions of the amelogenin gene on the human X and Y chromosomes; Sullivan et al, 1993) is likewise effective for sexing noninvasively collected samples of gorillas, chimpanzees, and gibbons. Although not broadly tested in other catarrhines, preliminary data suggest that this assay will not work without modification outside of the hominoids (Ensminger and Hoffman, 2002;Di Fiore, unpublished data). Nonetheless, Wilson and Erlandsson (1998) developed a general PCR-based sexing assay for anthropoid primates which takes advantage of a several hundred base-pair size difference between the X and Y homologues of the zinc finger protein gene, and this assay has been used successfully in studies of wild populations of several New World primates (e.g., Lagothrix: Di Fiore, 2002; Aotus: Gagneux, personal communication).…”
Section: Conservation Applicationsmentioning
confidence: 99%
“…With respect to PCR-based sex determination, for example, recently verified that the sexing assay commonly employed in human forensic cases (which is based on a 6-base-pair difference in length between homologous regions of the amelogenin gene on the human X and Y chromosomes; Sullivan et al, 1993) is likewise effective for sexing noninvasively collected samples of gorillas, chimpanzees, and gibbons. Although not broadly tested in other catarrhines, preliminary data suggest that this assay will not work without modification outside of the hominoids (Ensminger and Hoffman, 2002;Di Fiore, unpublished data). Nonetheless, Wilson and Erlandsson (1998) developed a general PCR-based sexing assay for anthropoid primates which takes advantage of a several hundred base-pair size difference between the X and Y homologues of the zinc finger protein gene, and this assay has been used successfully in studies of wild populations of several New World primates (e.g., Lagothrix: Di Fiore, 2002; Aotus: Gagneux, personal communication).…”
Section: Conservation Applicationsmentioning
confidence: 99%
“…In mammals, the sex-determining SRY and Zfx/y genes (Griffiths and Tiwari, 1993;Taberlet et al, 1993) and the enamel protein gene for amelogenin (Chen et al, 1999;Yamauchi et al, 2000;Bradley et al, 2001;Ensminger and Hoffman, 2002;Di Fiore, 2005) have been used to identify sex. Of these, amelogenin (AMEL) requires a single pair of primers only to amplify both X-and Y-linked alleles and shows a relatively large different in length between the X-and Y-chromosome fragments (Sullivan et al, 1993;Ennis and Gallagher, 1994;Yamauchi et al, 2000;Pfeiffer and Brenig, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in human molecular genetics has revealed that techniques developed for the genetic analyses of humans are applicable to the great apes because of their close genetic relationship (Moore et al 1991;Ensminger and Hoffman 2002). This fact is particularly advantageous, especially when considering the labor and time required to develop experimental techniques for individual species.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies will also allow for the estimation of effective population size, which is an important consideration for conservation management. Several loci have been utilized for sex identification in humans: amelogenin (AMG) (Sullivan et al 1993;Ensminger and Hoffman 2002), SRY (Taberlet et al 1996), DXZ4 (Naito et al 1993), ZFX/ZFY (Wioson and Erlandsson 1998) and DYZ1 (Akane et al 1991). The AMG gene includes a particular deletion within the locus on the Y chromosome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation